KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 3 PADANG - Sari, Debby Purnama; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2020)
ABSTRACT This article was written to describe the correlation of reading comprehension and writing a exposition text seventh grade students of SMA Negeri 3 Padang. Tipe of this research is quantitative research with descriptive method and used a correlational research schema. The population and sample of this research is the seventh grade students of SMA Negeri 3 Padang in the year of 2019/2020. The sample of this research is 40 students. The sampling technique used is random sampling. From this research, it can be concluded that there is significant correlation between reading comprehention with writing exposition text seventh grade students of SMA Negeri 3 Padang by freedom degree n-1 with significants rate 95% and tobservation is bigger than ttabel that is 3,78 > 1,68. It means, the students who have a higher ability in reading comprehension so they also have a good ability in write a exposition text. In contrast, if their ability in reading comprehension is low, their ability in write a exposition text is too low. Kata Kunci: Hubungan, Keterampilan, Membaca, Menulis, Teks Eksposisi